Чи існує в Україні школа юридичної візантиністики? - Харитонов, Євген Олегович; Харитонов, Є. О.; Kharytonov, Yevhen O.; Харитонова, Олена Іванівна; Харитонова, О. І.; Kharytonova, Olena I. (Одеса, 2019)
У статті досліджуються проблемні питання формування вітчизняної школи юридичної візантиністики, від існування якої залежить ефективність використання наукового потенціалу для забезпечення адаптації вітчизняного цивільного законодавства до права Європи в умовах інтеграційних процесів. На підставі аналізу стану речей у цій галузі, огляду наукових досліджень у галузі візантійського (греко-римського) права та проблем його рецепції у цивільному праві України обґрунтовано висновок, що наразі у вітчизняному правознавстві формування вітчизняної школи юридичної візантиністики ще не відбулося. Тому поки що може йтися лише про обрання певного напрямку досліджень, про спробу створення такої школи. Разом із тим висновок про наявність передумов створення наукової школи юридичної візантиністики дозволяє визначити завдання діяльності в цьому напрямку.

The article examines the problematic issues of the formation of the national school of legal Byzantine studies, the existence of which determines the effectiveness of the use of scientific potential to ensure the adaptation of domestic civil legislation to the law of Europe in the context of integration processes. The need for the scientific research concerning the Byzantine (Eastern European) tradition of law (the totality of which, to a certain extent, can be named here as “legal Byzantine studies”) is due, first of all, to the fact that the legacy of the Byzantine Empire at one time was partially broadcast to Kievan Rus, and with time, many scholars began to recognize that Ukraine objectively (together with Greece and Russia) was the main successor to the Byzantine heritage. The largest activity of research in the field of legal byzantinisties took place in about ten years – from 1997 to 2012 when theses were defended and a number of publications of domestic lawyers in this field appeared. The article also focuses on the “troistic” significance of Justinian’s systematization: as the basis for the formation and improvement of the Greco-Roman (Byzantine) law; as the empirical basis for the reception of Roman law in later legal systems; as a positive experience large in scope and successful in the systematization of law However, after ten years of active research (including dissertation), the interest of lawyers in issues related to the Byzantine legal system, the reception of Byzantine law, etc., has dropped markedly. After 2012, only a few publications appear in this area (not counting sections in comparative law teaching manuals, etc.). Based on the analysis of the state of affairs in this area, taking into account scientific research in the field of Byzantine (Greco-Roman) law and the problems of its reception in the civil law of Ukraine, the conclusion is substantiated that the formation of a national school of legal Byzantine studies has not yet occurred in Russian jurisprudence. Therefore, so far we can only talk about the election of a certain area of research, about an attempt to create such a school. At the same time, the conclusion that there are prerequisites for the creation of a scientific school of legal Byzantinistics allows determining the objectives of activities in this direction.

The article examines the problematic issues of the formation of the national school of legal Byzantine studies, the existence of which determines the effectiveness of the use of scientific potential to ensure the adaptation of domestic civil legislation to the law of Europe in the context of integration processes. The need for the scientific research concerning the Byzantine (Eastern European) tradition of law (the totality of which, to a certain extent, can be named here as “legal Byzantine studies”) is due, first of all, to the fact that the legacy of the Byzantine Empire at one time was partially broadcast to Kievan Rus, and with time, many scholars began to recognize that Ukraine objectively (together with Greece and Russia) was the main successor to the Byzantine heritage. The largest activity of research in the field of legal byzantinisties took place in about ten years – from 1997 to 2012 when theses were defended and a number of publications of domestic lawyers in this field appeared. The article also focuses on the “troistic” significance of Justinian’s systematization: as the basis for the formation and improvement of the Greco-Roman (Byzantine) law; as the empirical basis for the reception of Roman law in later legal systems; as a positive experience large in scope and successful in the systematization of law However, after ten years of active research (including dissertation), the interest of lawyers in issues related to the Byzantine legal system, the reception of Byzantine law, etc., has dropped markedly. After 2012, only a few publications appear in this area (not counting sections in comparative law teaching manuals, etc.). Based on the analysis of the state of affairs in this area, taking into account scientific research in the field of Byzantine (Greco-Roman) law and the problems of its reception in the civil law of Ukraine, the conclusion is substantiated that the formation of a national school of legal Byzantine studies has not yet occurred in Russian jurisprudence. Therefore, so far we can only talk about the election of a certain area of research, about an attempt to create such a school. At the same time, the conclusion that there are prerequisites for the creation of a scientific school of legal Byzantinistics allows determining the objectives of activities in this direction.
Харитонов Є. О. Чи існує в Україні школа юридичної візантиністики? / Є. О. Харитонов, О. І. Харитонова // Часопис цивілістики : наук.-практ. журн. / редкол.: С. В. Ківалов (голов. ред.), Є. О. Харитонов (заст. голов. ред.), К. Г. Некіт (відп. секр.) [та ін.]. - Одеса, 2019. – Вип. 32. – С. 6-12.
Keywords: наукова школа; науковий напрямок; наукові дослідження; візантиністика; адаптація права; інтеграційні процеси; scientific school; scientific direction; research; Byzantinistic; adaptation of law; integration processes; Research Subject Categories::LAW/JURISPRUDENCE; Research Subject Categories::SOCIAL SCIENCES